Some observations on viral hepatitis. - McCollum, R. W. (Yale Journal of Biology and Medicine, 1982)
Epidemiologic patterns of viral hepatitis continue to change over time. Our understanding of its behavior began to change with the recognition that multiple distinct etiologic agents (hepatitis viruses A, B, and non-A/non-B) produce similar clinical syndromes and that there is a broad variability of age-related host response to infection with a given agent. Dorothy Horstmann was among the first to point to the relative mildness of symptoms in children and to the potential epidemiologic significance of such infections. Although hepatitis type A appears to be on a steady decline in overall national incidence, there is an increasing recognition of adult cases epidemiologically related to relatively mild or inapparent infections among infants and children attending day-care centers.